Balancing Foreign Policy between Neighbors and Friends: The Case of Sri Lanka - Jayathilake, Anudi (Department of International Studies, Faculty of Social Sciences, University of Kelaniya, Sri Lanka, 2023)
The concept of Foreign Policy is vividly portrayed as a strategic sequence of activities within a global arena. States possess vivid foreign policies which are aimed to achieve National Interests along with a main consideration to economic, social, and cultural sectors. Sri Lanka‟s foreign policy is formulated on the basis of the policies of leaders. Different leaders have emphasized the importance of establishing healthy relations with the neighbors, India and friends, China. Mrs. Sirimavo Bandaranaike‟s foreign policy stands unique in balancing the foreign policy between neighbors and friends. This research paper extensively describes the Sri Lankan perspective of maintaining equilibrium in foreign policy focusing on the trailblazing foreign policy of the elegant leader Sirimavo Bandaranaike. Hence, the research paper vividly analyses on how the strategies employed by Mrs. Bandaranaike namely, shuttle diplomacy, balance of power and the policy of non- Alignment aided in balancing the foreign policy while encountering the changing nature of geopolitics. The vibrant research methodology includes a detailed data analysis via a specific range of primary and secondary sources which includes research papers, journal articles, books, letters, government documents, speeches, and interviews. Subsequently, this research becomes significant as it portrays an overview on the efficient maintenance of equilibrium of the Sri Lankan foreign policy and how the modern politicians could utilize the same strategies to address key issues. The specific research findings elaborate on the pivotal analysis on the establishment of strong and healthy relations with the Communist bloc via the strategy of “Balance of Power”. Thereby, it aims to counterbalance the Indian influence and reduce the interdependency. Hence, the vibrant research recommends the application of a Non-Aligned foreign policy strategically within modern politics.
Keywords: Foreign Policy, National Interests, Non-Alignment, Shuttle Diplomacy